Histopathological Patterns and Luminal Subtypes among Breast Cancer Patients in the Middle Euphrates Region of Iraq - Ahmed Mjali; Mustafa Majeed Obaid; Haider Hasan Jaleel Al-Shammari; Afnan Fouad Alwakeel; Alaa Othman Sedeeq; Nareen Tawfeeq Abbas; Layth Mula-Hussain (Asian Pacific Journal of Cancer Biology, 2022)
Objectives: To evaluate the pathological patterns & luminal subtypes of breast cancer patients in the Middle Euphrates region of Iraq. Methods: A retrospective descriptive study was conducted at Al-Hussein Cancer Center in Karbala province of Iraq between January 2012 and August 2020. Results: There were 920 female patients with breast cancer. At the time of diagnosis, the mean age was 50.20 ±11.74 years. The most frequent pathological subtype was invasive ductal carcinoma in 91.85%, and 50.32% of tumors were grade II. Of luminal subtypes, Luminal A was the most prevalent subtype in 53.69%. Conclusion: Our results were similar to middle eastern patterns but significantly differed from western patterns.